2015
DOI: 10.1007/s10653-015-9743-7
|View full text |Cite
|
Sign up to set email alerts
|

Inferring the fluoride hydrogeochemistry and effect of consuming fluoride-contaminated drinking water on human health in some endemic areas of Birbhum district, West Bengal

Abstract: This research work is carried out to evaluate fluoride (F) hydrogeochemistry and its effect on the population of two endemic villages of Birbhum district, West Bengal. Fluoride concentration in drinking water varies from 0.33 to 18.08 mg/L. Hydrogeochemical evolution suggests that ion-exchange mechanism is the major controlling factor for releasing F in the groundwater. Most of the groundwater samples are undersaturated with respect to calcite and fluorite. Health survey shows that out of 235 people, 142 peopl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(13 citation statements)
references
References 28 publications
(25 reference statements)
0
11
1
Order By: Relevance
“…[ 15 ] and Mondal et al . [ 16 ] The present study is in contrast with Broadbent et al . [ 17 ] study results, where there was no apparent difference in IQ because of fluoride exposure.…”
Section: Discussioncontrasting
confidence: 99%
“…[ 15 ] and Mondal et al . [ 16 ] The present study is in contrast with Broadbent et al . [ 17 ] study results, where there was no apparent difference in IQ because of fluoride exposure.…”
Section: Discussioncontrasting
confidence: 99%
“…8,11,17 Trivedi et al, reported that an elevated fluoride level would affect higher levels of intelligence more vigorously than normal and low intelligence levels. 18 There was contrast reports presenting a statistically significant difference in IQ levels of children belonging to high, medium, and low fluoride areas, by Khan et al and Mondal et al 5,6 The functional and biochemical harm to the nervous system during the prenatal and development periods of infancy and childhood because fluoride can cross the blood brain barrier leading to lack of IQ in children exposed to high levels of fluoride is mainly; however, it is also due to factors involving variation in biological susceptibility, environmental conditions, and measurement errors. 19 Xiang et al, discussed about decreasing IQ with increasing age but reason is still not clear.…”
Section: Discussionmentioning
confidence: 92%
“…This denotes higher mal occlusion. Intelligence level was clubbed into grade (3)(4)(5) and (1-2) due to very small number in each cell. The comparison between low (3-5) and high (1-2) level of intelligence observed that risk of high fluoride level with relation to poor intelligence grade was insignificant (OR: 1.34; 95%CI: 0.72-2.49) ( Table 2).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Fordyce et al (2007) reported that high fluoride concentration in the environment might be due to various man made activities such as coal and aluminum industries, use of fertilizer and manufacturing process. Mondal et al (2016) reported -1 fluoride concentration above 1.5 mg l carry an increasing risk of dental and skeletal fluorosis, as well as osteoporosis disease in women. (Min et al, 2002).…”
Section: Resultsmentioning
confidence: 99%